Penerapan Model Problem Based Learning pada Mata Pelajaran Dasar Listrik dan Elektronika di Sekolah Menengah Kejuruan - Muhammad Gunalan; Mukhlidi Muskhir (Jurnal Pendidikan Teknik Elektro, 2020)
This study aims to see the impact of applying the PBL (Problem Based Learning) model to the learning outcomes of class X students majoring in Electric Power Installation Engineering (TTL), amounting to 30 people. The achievement of student learning outcomes in knowledge competence is still disappointing with an average student score of 57.6. One of the reasons is the teacher-centered learning techniques still being applied by the teacher. As a result, students have difficulty in understanding the material which results in students' dislike for certain subjects. This study uses an experimental method with pre-experimental type One-Group Pretest-Posttest Design. Based on the results of the study, there was an increase in student learning outcomes in knowledge competencies with an average of 73.13. Based on the results of the analysis of the formula effect size can be seen the results of the pretest with a posttest worth 1.43 with the category of Large (Large Effect)